2013
DOI: 10.1016/j.brat.2013.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in recovery from PTSD in male and female interpersonal assault survivors

Abstract: Men and women differ in exposure to trauma and the development of posttraumatic stress disorder (PTSD); however, research regarding sex differences in recovery from PTSD has been sparse. This study evaluated the treatment response trajectory for 69 male and female interpersonal assault survivors, using a modified Cognitive Processing Therapy (CPT) protocol that allowed survivors to receive up to18 sessions of CPT, with treatment end determined by therapy progress. Few sex differences were observed in trauma hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
50
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 52 publications
7
50
0
1
Order By: Relevance
“…The findings from this study were consistent with previous findings that women with PTSD, on average, had lower aggressive/violent symptoms, but higher comorbid severity of depressive symptoms than men with PTSD (e.g., Galovski et al., ; Maguen et al., ). Having more depressive symptoms was probably related to our finding that women also had lower quality of life than men at treatment initiation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings from this study were consistent with previous findings that women with PTSD, on average, had lower aggressive/violent symptoms, but higher comorbid severity of depressive symptoms than men with PTSD (e.g., Galovski et al., ; Maguen et al., ). Having more depressive symptoms was probably related to our finding that women also had lower quality of life than men at treatment initiation.…”
Section: Discussionsupporting
confidence: 92%
“…Men and women might react to sexual assault and trauma differently. In both veteran and nonveteran populations, women showed more severe PTSD and depressive symptoms, whereas men reported more subsequent substance abuse and anger/aggression (Galovski, Blain, Chappuis, & Fletcher, ; Maguen et al., ; Zlotnick, Zimmerman, Woldsdorf, & Mattia, ). Sexual assault might have an impact on the victim's sexual identity, masculinity/femininity, and self‐concept (Mezey & King, ; Walker, Archer, & Davies, ).…”
mentioning
confidence: 99%
“…We also focused on female survivors in this study, although peritraumatic TI is not gender-specific. In fact, male survivors might be at heightened risk for negative cognitions and anger toward the self following sexual assault (e.g., Galovski, Blain, Chappuis, & Fletcher, 2013), and might in particular misinterpret the TI response as personal weakness. Additional research on other forms of cognitive peritraumatic distress such as dissociation has been largely inconclusive regarding the effects of dissociation on PTSD symptoms (e.g., Dalenberg et al, 2012; Otis, Marchand, & Courtois, 2012), and our findings indicate that dissociation and other cognitive components of peritraumatic distress such as perceived inescapability are distinct phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in treatment outcome remained even after controlling for initial OCD severity and psychosocial functioning. Finally, a study on cognitive processing therapy in patients with PTSD found that males and females did not differ significantly on the primary outcomes of PTSD and depression [59]. This was found both following the last session and at 3 months follow-up in spite of medium effect sizes favouring females.…”
Section: Psychotherapymentioning
confidence: 93%
“…One study reported comparable attrition rates and treatment length for males and females undergoing cognitive processing therapy for PTSD [59]. Other studies have found that males are more likely than females to drop out of treatments including aspects of exposure [26,51,57].…”
Section: Psychotherapymentioning
confidence: 99%